Panel Analysis of Calendar Anomalies in the South African Stock Market: Array - Mazviona, Batsirai Winmore; Mah, Gisele; Choga, Ireen (Acta Universitatis Danubius. Œconomica, 2021)
Calendar anomalies in stock markets play a paramount role is explaining stock returns dynamics. The objective of this study is to determine whether day of the week, turn of the month, holiday and January seasonality exists in the South African stock market. The Johannesburg stock exchange indices data comprised of Top 40, All Shares, Basic Materials, Industrials, Consumer Goods, Health Care, Consumer Services, Telecommunications, Financials and Technology covering the period 1995-2018. Pooled panel with Arellano robust standard errors model was employed. The pooled panel model with Arellano robust estimates results for the day of the week revealed a positive Monday effect. A positive turn of the month effect was observed. Positive post-holiday was found. The results revealed October effect. The study recommends that investors trade on Mondays to earn the highest return during the week. Investors have the potential to earn excess returns when they invest on turn of the month period. For the holiday strategy, investors should trade on the day after the holiday since will entail more profits from the investment. Investors can earn more money through trading in October than in January. The existence of calendar anomalies in the South African equity market invalidates efficient market hypothesis. The novelty of the study lies in the use of sectorial indices in assessment calendar anomalies in a developing stock market.